2018
DOI: 10.7717/peerj.4370
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of progress and promise of induced pluripotent stem cells: historical origins, characteristics, mechanisms, limitations, and potential applications

Abstract: The discovery of induced pluripotent stem cells (iPSCs) by Shinya Yamanaka in 2006 was heralded as a major breakthrough of the decade in stem cell research. The ability to reprogram human somatic cells to a pluripotent embryonic stem cell-like state through the ectopic expression of a combination of embryonic transcription factors was greeted with great excitement by scientists and bioethicists. The reprogramming technology offers the opportunity to generate patient-specific stem cells for modeling human disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 223 publications
(323 reference statements)
0
112
0
1
Order By: Relevance
“…Nonetheless, to what extend these iPSCs are uniformed in their quality remain in question. Moreover, during iPSCs establishment, reprogramming efficiency is depended on donor-cell-type and reprogramming method [73,74]. The optimum somatic cell type for reprogramming into iPSCs and subsequent differentiation into NSCs remains to be determined.…”
Section: Challenges Surrounding Nsc Transplantationmentioning
confidence: 99%
“…Nonetheless, to what extend these iPSCs are uniformed in their quality remain in question. Moreover, during iPSCs establishment, reprogramming efficiency is depended on donor-cell-type and reprogramming method [73,74]. The optimum somatic cell type for reprogramming into iPSCs and subsequent differentiation into NSCs remains to be determined.…”
Section: Challenges Surrounding Nsc Transplantationmentioning
confidence: 99%
“…This also implies that only a minority of studies (22.9%) were of an interventional study type, where cells were actually transplanted into patients for therapeutic purposes. From the view point of translational medicine, these interventional studies are of greater interest, since the introduction of the iPSC technology was associated with a signi cant hope for future clinical use in the sense of cellular transplantation (8,(47)(48)(49)(50). While the total number of clinical trials involving iPSCs (74.8%) was substantially higher than the ones involving ESCs (25.2%), the picture changes completely when focusing on interventional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery that somatic cells could be reprogrammed to iPSCs in 2006 by Yamanaka and colleagues , vast amount of research has be performed to try to improve the reprogramming efficiency and to better understand the molecular machinery of pluripotency acquisition and maintenance. Undoubtedly, numerous studies which reported identification of a new effectors or barriers of reprogramming process have broaden our knowledge about complex interaction of the different signaling pathway and reprogramming mechanisms and have highlighted an important role for MET, metabolism, apoptosis, cytoskeleton rearrangement, autophagy, immune response, cell cycle alterations, epigenetics, and many others for the effective hiPSCs generation.…”
Section: Discussionmentioning
confidence: 99%